(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2021)
The arrangement of cover crop on the soil surface is a fundamental practice for the establishment of soil and water conservation systems. The objective of the study was to evaluate the effect of different cover crops, on runoff and quality of runoff using a portable rain simulator with simple construction and operational characteristics. The experiment was carried out at the School Farm of the IF Goiano Campus Iporá in a Quartzipsament, in a Brazilian Savanna region. The following uses and land cover were evaluated: uncovered soil, single hybrid corn and crop-livestock system (Santa Fé System). To determine the runoff volume and the runoff quality in each cover, three tests per treatment were performed, using a pendulum rainfall simulator built at the IF Goiano Campus Iporá. The collection of runoff was made in 1L containers with an interval of five minutes, each sampled volume was divided into three sub-samples to determine the turbidity, pH and conductivity of the runoff. The cover crop that presented the best performance with less runoff volume and better quality of the runoff when the turbidity was evaluated, was the crop-livestock system, which demonstrates its high potential in minimizing soil water erosion.